Kecenderungan Konsumsi Marginal di Kalangan Masyarakat Indonesia - Riani, Novya Zulva (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT This article analyzes the marginal propensity to consume among Indonesia people as well as linking with the national income and interest rate variables. The analysis showed that the value of the MPC (marginal propensity to consume) among Indonesian people in the period of 1995-2009 has been changed following the volatile economic fluctuations at the time. In the period of 1995 -1998 MPC value is around 0.73, while the value of the MPC in the period 1999-2002 is around 0.39, and the MPC in the period 2004-2009 is around 0.48. These fluctuations are due to fluctuating income and an increase in domestic interest rates that provide a major influence on the fluctuations change propensity to consume. Kata kunci: Konsumsi Marginal, Pendapatan Nasional, Tingkat Bunga